Mitochondrial DNA variants in inclusion body myositis characterized by deep sequencing. (27th May 2021) - Hedberg‐Oldfors, Carola; Lindgren, Ulrika; Basu, Swaraj; Visuttijai, Kittichate; Lindberg, Christopher; Falkenberg, Maria; Larsson Lekholm, Erik; Oldfors, Anders
Abstract: Muscle pathology in inclusion body myositis (IBM) typically includes inflammatory cell infiltration, muscle fibers with rimmed vacuoles and cytochrome c oxidase (COX)‐deficient fibers. Previous studies have revealed clonal expansion of large mitochondrial DNA (mtDNA) deletions in the COX‐deficient muscle fibers. Technical limitations have prevented complete investigations of the mtDNA deletions and other mtDNA variants. Detailed characterization by deep sequencing of mtDNA in muscle samples from 21 IBM patients and 10 age‐matched controls was performed after whole genome sequencing with a mean depth of mtDNA coverage of 46, 000x. Multiple large mtDNA deletions and duplications were identified in all IBM and control muscle samples. In general, the IBM muscles demonstrated a larger number of deletions and duplications with a mean heteroplasmy level of 10% (range 1%‐35%) compared to controls (1%, range 0.2%‐3%). There was also a small increase in the number of somatic single nucleotide variants in IBM muscle. More than 200 rearrangements were recurrent in at least two or more IBM muscles while 26 were found in both IBM and control muscles. The deletions and duplications, with a high recurrence rate, were mainly observed in three mtDNA regions, m.534‐4429, m.6330‐13993, and m.8636‐16072, where some were flanked by repetitive sequences. The mtDNA copy number in IBM muscle was reduced to 42% of controls. Immunohistochemical and western blot analyses of IBM muscle revealed combined complex I and complex IV deficiency affecting the COX‐deficient fibers. In conclusion, deep sequencing and quantitation of mtDNA variants revealed that IBM muscles had markedly increased levels of large deletions and duplications, and there were also indications of increased somatic single nucleotide variants and reduced mtDNA copy numbers compared to age‐matched controls. The distribution and type of variants were similar in IBM muscle and controls indicating an accelerated aging process in IBM muscle, possibly associated with chronic inflammation. Abstract : Muscle pathology in inclusion body myositis (IBM) typically includes cytochrome c oxidase‐deficient muscle fibers indicating mitochondrial DNA defects. Deep sequencing and quantification of mtDNA variants revealed that IBM muscles had markedly increased levels of large deletions and duplications and reduced mtDNA copy numbers compared to age‐matched controls. The distribution and type of variants were similar in IBM muscle and controls indicating an accelerated aging process in IBM muscle.